Imunoexpressão de C4D em transplantados renais: estudo retrospectivo com avaliação de sua relação com variáveis clínicas e morfológicas - Oliveira, Adriana Regina Vilarinho de (2022)
Antibody-mediated rejection represents a significant and ongoing challenge to long-lasting graft survival in renal transplantation and is considered the leading cause of long-term graft loss. Detection of C4d in biopsies is an important adjunctive tool to help understand the alloimmune response and, in particular, to diagnose antibody-mediated rejection. The aim of this study was to evaluate and investigate whether the expression of C4d is related to clinicopathological variables, with an emphasis on rejection of the allograft or not, as well as to evaluate the histological alterations in transplanted kidney biopsies and their relationship with the evolution of the graft. Biopsies and C4d immunohistochemistry expression from 22 patients who underwent kidney transplantation between 2013 and 2014 were analyzed, with a follow-up period of at least 1 year. Follow-up biopsies from patients which underwent renal transplant for a longer period of time showed worsening of the Banff criteria for chronicity. Patients who maintained C4d staining throughout the course of transplant showed a strong association with proteinuria. All cases with proteinuria maintained unchanged C4d status, with p<0.032. The vast majority of cases with mild lesion (i=1) maintained C4d status and the only case with maximum score (i=3) showed an increase in C4d expression.When comparing different post-transplant biopsies time point, biopsies performed in the follow-up showed a worsening of the Banff scores, both in terms of activity and chronicity criteria, and the maintenance of the C4d status was strongly associated with proteinuria.